The Incidence, Management, and Outcome of Penetrating Bladder Injuries in Civilians Resultant from Armed Conflict in Baghdad 2005-2006 - Firas G. Petros; Richard A. Santucci; Naimet K. Al-Saigh (Advances in Urology)
The purpose of this paper is to review the diagnosis, treatment, and outcomes of penetrating bladder injuries suffered by civilians in the Iraqi war zone. Materials and Methods. All civilian trauma cases received alive at Al-Yarmouk Teaching Hospital from January 2005 to August 2006 were reviewed for the presence of bladder injury. Results. 533 cases of penetrating abdominal trauma were identified, of which 177 (33%) involved the genitourinary (GU) system and 64 (12%) involved the bladder. Most (70%) were young males, and most (55%) had grade IV injuries. Associated injuries occurred in 63/64 (98%) of patients. 3 patients had missed bladder injuries, and all of these had complications related to their missed injury. Bladder-related complications occurred in 11% of cases, and mortality in 13%, all due to extravesical injuries. Conclusions. Penetrating bladder injury among civilians in Baghdad war zone resulted in 64 cases in 18 months. The initial detection rate is very high (98%), and after primary repair, lasting complications are rare. Morbidities from missed injuries were severe hematuria and vesicorectal fistula. However, (3%) of vesicorectal fistulae healed spontaneously with prolonged bladder drainage. Associated injuries are the rule in penetrating bladder injury patients, and must be diligently investigated and treated.